Content validity study: instrument development to measure professional learning communities through lesson study - M Lukitasari; R Hasan; J Handika; C Primiani; P Pujiati; N K Dewi; W Widiyanto; W Murtafiah (International Conference on Mathematics and Science Education of Universitas Pendidikan Indonesia, 2018)
Professional Learning Community (PLC) in lesson study (LS) is a development ofteacher professionalism which is very important to support the learning process of the 21century. The research aims to develop a practical instrument to be used to measure affectivity and achievement of PLC-LS from a group of teachers during lesson study activity. This research was carried out of two-step validity content process namely, development and evaluation. Thefirst step was done by determining the indicator and descriptor. The second step was done through obtaining feedback from the expert related to the developed instrument. This research produced an instrument with six indicators outlined in 46 questions related to PLC namely, six reflective questions, seven collaborative questions, seven learning outcome questions, nine share value and vision questions, eight collective responsibility questions, and nine development effective leadership questions which have been validating to be implemented. Based on the CV1 analysis, there are 7 items that show below 0,6 score which is then being left out while 11 others with the score more than 0,6 were revised according to experts’ recommendations. The result ofCVR is 0.82 which shows that the instrument of PLC-LS is valid and can be used.